Transformational Devices of the Inner Form of a Word (Kinds of Unscientific Etymology) - Vvedenskaja, Liudmila A.; Kolesnikov, Nikolaj P. (Respectus Philologicus, 2003)
Having examined various definitions of folk etymology offered by different researchers and presented in dictionaries, directories, manuals, the authors came to the conclusion that it is necessary to specify the borders of a concept and differentiate the adjacent phenomena. All phonetic changes in a word in a case of folk etymology should necessarily result in occurrence of some meaning that was absent before its transformation. Not taking into account this condition it is impossible to consider phonetic changes as folk-etymological ones. For the adjacent phenomena the concepts of pseudo-folk etymology (a deliberate distortion of a word for stylistic purposes), children's etymology, and pseudo-etymology are being introduced.
Keywords: lexical meaning; inner form of the word; motivation; etymology; folk etymology